5xFAD mice do not have myenteric amyloidosis, dysregulation of neuromuscular transmission or gastrointestinal dysmotility. Issue 12 (5th August 2022) - Yelleswarapu, Narayana Krishna; Masino, Marlene; Henderson, Skye; Fernandes, Roxanne; Swain, Greg; Galligan, James J.; Xu, Hui
Abstract: Background: Alterations in gastrointestinal (GI) function and the gut‐brain axis are associated with progression and pathology of Alzheimer's Disease (AD). Studies in AD animal models show that changes in the gut microbiome and inflammatory markers can contribute to AD development in the central nervous system (CNS). Amyloid‐beta (Aβ) accumulation is a major AD pathology causing synaptic dysfunction and neuronal death. Current knowledge of the pathophysiology of AD in enteric neurons is limited, and whether Aβ accumulation directly disrupts enteric neuron function is unknown. Methods: In 6‐month‐old 5xFAD (transgenic AD) and wildtype (WT) male and female mice, GI function was assessed by colonic transit in vivo; propulsive motility and GI smooth muscle contractions ex vivo; electrochemical detection of enteric nitric oxide release in vitro, and changes in myenteric neuromuscular transmission using smooth muscle intracellular recordings. Expression of Aβ in the brain and colonic myenteric plexus in these mice was determined by immunohistochemistry staining and ELISA assay. Key Results: At 6 months, 5xFAD mice did not show significant changes in GI motility or synaptic neurotransmission in the small intestine or colon. 5xFAD mice, but not WT mice, showed abundant Aβ accumulation in the brain. Aβ accumulation was undetectable in the colonic myenteric plexus of 5xFAD mice. Conclusions: 5xFAD AD mice are not a robust model to study amyloidosis in the gut as these mice do not mimic myenteric neuronal dysfunction in AD patients with GI dysmotility. An AD animal model with enteric amyloidosis is required for further study. Abstract : Amyloidosis in central and enteric nervous system contribute to congenic impairment and gastrointestinal dysmotility in Alzheimer's Disease (AD). 5xFAD mice, a transgenic mouse model of AD, mimic the amyloidosis in central nervous system but lacking amyloidosis in enteric nervous system.